2019
DOI: 10.1002/ar.24076
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Palatal Shelf Elevation During Secondary Palate Formation

Abstract: Palatal shelf elevation is an essential morphogenetic process during secondary palate formation. It has been proposed that shelf elevation results from an intrinsic elevating force and is regulated by extrinsic factors that are associated with development of other orofacial structures. Although dynamic palate culture is a common in vitro approach for studying shelf elevation, it requires the tongue or the tongue and mandible to be removed before culture, which prevents any determination of the role of the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Currently, the understanding of the mechanism of shelf elevation is mainly based on histomorphological studies from 2D sections and various in vitro studies. 6 , 7 , 9 , 24 , 31 – 33 However, conventional 2D histology provides only planar information of the PS and surrounding tissues. Furthermore, there were no definite sites or anatomical landmarks of the anterior, middle (the presumptive hard palate), and posterior (the presumptive soft palate) regions of the palate, which were inconsistent in various articles and might give rise to misinterpretations and the loss of crucial shelf morphological change during palatal elevation along the AP axis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the understanding of the mechanism of shelf elevation is mainly based on histomorphological studies from 2D sections and various in vitro studies. 6 , 7 , 9 , 24 , 31 – 33 However, conventional 2D histology provides only planar information of the PS and surrounding tissues. Furthermore, there were no definite sites or anatomical landmarks of the anterior, middle (the presumptive hard palate), and posterior (the presumptive soft palate) regions of the palate, which were inconsistent in various articles and might give rise to misinterpretations and the loss of crucial shelf morphological change during palatal elevation along the AP axis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, forces generated by HA hydration within the palatal tissue may help overcome the initial blockade by the tongue during normal palatogenesis, allowing the palate to displace the tongue dorsally in a timely manner; although this force is not required for the eventual shelf elevation. 178 , 179
Fig. 4 Mechanical regulation of palatal shelf elevation and fusion.
…”
Section: Part II Shaping Craniofacial Structures By Forces and Matermentioning
confidence: 99%
“…Palatal shelf elevation results from an endogenous factor that remodels mesenchyme, but the source of the factor remains unknown (9)(10)(11). A recent study reported that actin cytoskeleton aligned substantially in palatal mesenchymal cells of elevating PSs (9).…”
Section: Introductionmentioning
confidence: 99%